Job stress and needlestick injuries in nurses: a retrospective observational study: Job stress and needlestick injuries in nurses - d'Ettorre, Gabriele; Greco, Mariarita (Acta Biomedica Atenei Parmensis, 2020)
Background: The prevention of needlestick injuries (NSIs) in nurses employed in Emergency Departments (EDs) represents a special issue for healthcare organizations globally. Stressful working conditions, lack of organizational arrangements and lack of supporting one another at work, may contribute to increase the risk of NSIs. Methods: We conducted an observational study to analyze: 1) the effectiveness of organizational interventions to minimize the occurrence of NSIs in ED nurses; 2) to measure the impact of such interventions on the safety budget. Results: The occurrence of NSIs detected after organizational level interventions was significantly lower than the occurrence observed previously such interventions (p